The Association between 25-Hydroxyvitamin D and Hemoglobin A1c Levels in Patients with Type 2 Diabetes and Stage 1–5 Chronic Kidney Disease. (27th August 2014) - Kajbaf, Farshad; Mentaverri, Romuald; Diouf, Momar; Fournier, Albert; Kamel, Said; Lalau, Jean-Daniel
Abstract : Aim . To examine the relationship between plasma 25-hydroxyvitamin D (25(OH)D) levels and blood hemoglobin A1c (HbA1c) levels in diabetic patients at various stages of chronic kidney disease (CKD). Methods . We screened for data collected between 2003 and 2012. The correlation between 25(OH)D and HbA1c levels was studied in patients categorized according to the severity of CKD and their vitamin D status. A multivariate linear regression model was used to determine whether 25(OH)D and HbA1c levels were independently associated after adjustment for a number of covariates (including erythrocyte metformin levels). Results . We identified 542 reports from 245 patients. The mean HbA1c value was 6.7 ± 1.0 % in vitamin D sufficiency, 7.3 ± 1.5 % in insufficiency, and 8.4 ± 2.0 % in deficiency (P < 0.0001 ). There was a negative correlation between 25(OH)D and HbA1c levels for the population as a whole (r = - 0.387, P < 0.0001 ) and in the CKD severity subgroups (r = - 0.384, P < 0.0001 and r = - 0.333, P < 0.0001 for CKD stages 1–3 and 4-5, resp.). In the multivariate analysis, the 25(OH)D level was the only factor associated with HbA1c (P < 0.0001 ). Conclusion . 25(OH)D levels were negatively correlated with HbA1c levels independently of study covariates.